Kerja Kelompok dalam Kegiatan Berbicara - Rian Muhamad Apriandi; Eva Fitriani Syarifah; Afief Fakhruddin (Journal of Language Education (JoLE), 2022)
There are a lot of problems and difficulties that face by students in the speaking activities. Teacher need a learning technique to apply especially in speaking activities and teacher often use is the grouping technique thus the teacher assigns them a group to work with which students have their own perception towards group work in speaking activities. This study aimed to know how teacher implement group work in speaking activities and to find out students perception on group work in speking activities. This research is a case study research using a qualitative approach. The participants of this study were 26 tenth-grade students in one of the senior high schools in Majalengka. The results showed that teacher implemented group work in speaking activities and have five steps to implemented it, and the students perception on group work is that there are advantages doing group work in speaking activities, indicating that students have a positive perception on group work in speaking activities. Although there are perceptions of group work have many advantage, students also have the perceptions of group work in speaking activities have disadvantage. Students feel like there are a group member that doesn’t contribute much in the group especially in speaking activities. However students feel there are disadvantage on group work in speaking activities but it still cannot compare with the many advantage on the implementation of group work in speaking activities.